Metabolomics of Non-muscle Invasive Bladder Cancer: Biomarkers for Early Detection of Bladder Cancer - Cheng, Xiangming; Liu, Xiaoyan; Liu, Xiang; Guo, Zhengguang; Sun, Haidan; Zhang, Mingxin; Ji, Zhigang; Sun, Wei (Frontiers in Oncology, 2018)
Background Clinical outcomes of bladder cancer (BC) is tightly associated with the stage and grade of initial diagnosed BC so that early detection is clearly important for patients with BC. However, diagnostic capability of current detective methods, such as urinary cytology, cystoscopy, imageology method and several urine-based tests, is insufficient. The objective of our study is to discover novel biomarkers for early stage of BC, called non-muscle invasive (NMI) BC, using liquid chromatography-high resolution mass spectrometry (LC-HRMS)-based metabolomics. Methods First morning midstream urine samples were collected from healthy adult and NMIBC patients. LC-HRMS was applied to distinguish NMIBC group without hematuria from the controls (gender- and age-matched volunteers with normal clinically healthy index), low-grade NMIBC from the controls and high-grade from low-grade NMIBC. Results A total of 284 subjects were enrolled in our study including 117 healthy adults, 80 NMIBC patients without hematuria and 87 NMIBC patients with hematuria. The metabolite panel including dopamine 4-sulfate, MG00/1846Z,9Z,12Z,15Z/00, aspartyl-histidine, tyrosyl-methionine was found in discovery set, which showed the predictive ability to distinct NMIBC group from the control group with area under the curve (AUC) of 0.838 in external validation set. AUC of the panel for low-grade NMIBC samples consisted of 3-hydroxy-cis-5-tetradecenoylcarnitine, 6-ketoestriol, beta-cortolone, tetrahydrocorticosterone and heptylmalonic acid was 0.899. The sensitivity and specificity were 0.881 and 0.786, respectively. AUC of the panel for distinction low-grade NMIBC versus high-grade NMIBC with and without hematuria were 0.827 and 0.755, respectively. In addition, metabolites involved in tryptophan metabolism were up-regulated in the urine of high-grade NMIBC patients compared with low-grade NMIBC patients with the presence or absence of hematuria. Conclusion NMIBC urine metabolic profiling was able to be applied for early detection of BC. Panels of metabolites were discovered to have potential value for NMIBC and low-grade NMIBC diagnosis as well as for NMIBC grading distinction.